Prevalence of Risk for Orthorexia in Athletes Using the ORTO-15 Questionnaire: A Systematic Mini-Review - Paludo, Ana Carolina; Magatão, Marina; Martins, Hilana Rickli Fiuza; Martins, Marcos Vinícius Soares; Kumstát, Michal (Frontiers in Psychology, 2022)
The article aims to summarize the literature about the profile of risk of orthorexia in athletes using the ORTO-15 questionnaire. The search was performed at PubMed, Embase, Web of Science, and Sport Discus databases, using the terms “orthorexia” AND “athletes” with the respective entry terms. A multistage process of selection followed the PRISMA 2020 recommendation. A total of 688 articles were identified, and six studies were available for the final process. The prevalence of risk for orthorexia was assessed by the articles by the ORTO-15 questionnaire and ranged between 38 and 35 points. The comparison between male and female athletes and, athletes and non-athletes was not significant in the six articles. In conclusion, the review highlights that athletes from different sports, included in the review, do not present a risk of orthorexia nervosa considering the cutoff of 40 points, but not 35 points. Also, athletes present the same orthorexic behavior compared to non-athletes, demonstrating that orthorexia is an issue that needs to be considered in the general population. Moreover, a special focus should be given on the ORTO-15 questionnaire, about the sensitivity to diagnose the prevalence of orthorexia, especially in athletes.